Upaya Meningkatkan Pemahaman Konsep Matematika Siswa Melalui Penerapan CORE di SMKN 2 Mataram - Nurlaelah; Sri Yuliyanti; Eliska Juliangkary (Jurnal Kependidikan Ki Hajar Dewantara, 2026)
Abstract: The aim of this research is to increase students' understanding of mathematical concepts through the application of CORE (Connecting, Organizing, Reflecting, Extending) at SMKN 2 Mataram. This research is classroom action research (PTK) which was carried out in two cycles and had four stages, namely action planning, action implementation, observation and reflection. The research subjects were students of class X RPL I SMKN 2 Mataram, totaling 32 students. The research instruments used were observation sheets and test sheets. The techniques for collecting data in this research are test techniques and observation techniques. There are two data analysis techniques used, namely quantitative and qualitative data analysis techniques. The result of this research is an increase in understanding of mathematical concepts for class X RPL I SMKN 2 Mataram students after implementing CORE learning capital. The test results increased students' understanding of mathematical concepts in cycle I by 50% (fair) while in cycle II it increased to 93.75% (very good). Observation results in cycle I were 65% (good) and observation results in cycle II were 100% (very good). Thus, it can be concluded that this study shows that the implementation of the CORE (Connecting, Organizing, Reflecting, and Extending) model in mathematics learning at SMKN 2 Mataram can significantly improve students' understanding of mathematical concepts. It is hoped that this research can become a reference for developing better similar research.